Creative practice inquiry in architecture - Mason, Ashley; Sharr, Adam (Abingdon, Oxon : Routledge, 2022)
"This collection introduces, illustrates, and advances fresh ideas about creative practice inquiry in architecture. It concerns architectural knowledge: how architects can use their distinctive skills, habits, and values to advance professional insight, and how such insights can be extended to make wider contributions to society, culture, and scholarship. It shows how architectural ways of knowing and working can be mobilised as tools for research. Collected here are a series of creative practices that emerge out of architecture and actively engage with other fields and methods reaching across the academic landscape. Architectural inquiries collected in this book probe matters that lie beyond the obvious expectations, the conventions, the default, of the discipline. Drawing, borrowing, adapting, dramatising, perhapsing, monstering, experimenting, cartooning-the tools and methods of each inquiry vary but they all share a common outward gaze, engaging architectural ways of knowing with other disciplines and practices including the arts, biological sciences, ethnography, and technology. Chapters gathered here offer insight not only into incipient modes and tools of architectural research, but emerging ethical, practical, and philosophical positions intimately tied to the creative practices involved. Setting-out the idea of creative practice inquiry in architecture, this innovative volume offers a lively and resourceful contribution to a growing body of work on design as research. It will be of interest to: students keen to pursue architectural ways of thinking and writing; practitioners who want to use their distinctive professional abilities to contribute to architectural and scholarly knowledge; and academics and doctoral candidates keen to engage with the burgeoning scholarly field of design research"--
Exposition and the staging of encounter: on assessing unconventional research outputs / Rolf Hughes -- Archival practices -- Office practices -- Building practices -- Studio practices -- Machine practices -- Out of bounds: methods and outputs of the architect-researcher / Katie Lloyd Thomas.
Includes bibliographical references and index.
Keywords: Architecture -- Research; Research -- Methodology